Consolationscapes in the face of loss : grief and consolation in space and time - Jedan, Christoph; Maddrell, Avril, 1964-; Venbrux, Eric (Abingdon, Oxon : Routledge, 2019)
And tentative conclusionReferences; 4. The crematorium as a ritual and musical consolationscape; Introduction; Music and the cremation ritual; Interference of places: Building, ritual and music; Music and consolation; Crematorium, music and consolation; Consolationscape; References; 5. Emotional landscapes: Battlefield memorials to seventeenthcentury Civil War conflicts in England and Scotland; Introduction; Emotional communities; Naseby (1645); Wigtown (1685); Emotional geographies; The Naseby monuments; Wigtown monuments; Conclusion; References
When the turtles vanishedRitual cleansing of the dead's territory; Postfuneral rites from Pirlangimpi to Karumurarimili; Conclusion; References; 8. Rituals, healing and consolation in post-conflict environments: The case of the Matabeleland Massacre in Zimbabwe; Introduction; Death wounds; The case of Gukurahundi; The practice of Ndebele traditional funeral rites; Gukurahundi and the desecration of religio-cultural values; Conclusion; References; 9. Love the dead, fear the dead: Creating consolationscapes in postwar northern Uganda; Introduction; Acholi consolationscapes
The LRA war and the displaced dead
OCLC-licensed vendor bibliographic record.
Keywords: Mourning customs; Consolation; Memorial rites and ceremonies; Bereavement; SOCIAL SCIENCE / Death & Dying; SCIENCE / Earth Sciences / Geography; SOCIAL SCIENCE / Human Geography